The Role of Mast Cells in Tuberculosis: Orchestrating Innate Immune Crosstalk? - Garcia-Rodriguez, Karen M.; Goenka, Anu; Alonso-Rasgado, Maria T.; Hernández-Pando, Rogelio; Bulfone-Paus, Silvia (Frontiers in Immunology, 2017)
Tuberculosis (TB) causes more annual deaths globally than any other infectious disease. However, progress in developing novel vaccines, diagnostics and therapies has been hampered by an incomplete understanding of the immune response to Mycobacterium tuberculosis (Mtb). While the role of many immune cells has been extensively explored, mast cells (MCs) have been relatively ignored. MCs are tissue resident cells involved in defense against bacterial infections playing an important role mediating immune cell crosstalk. This review discusses specific interactions between MCs and Mtb, their contribution to both immunity and disease pathogenesis and explores their role in orchestrating other immune cells against infections.